2012 IEEE International Symposium on Mixed and Augmented Reality (ISMAR) 2012
DOI: 10.1109/ismar.2012.6402573
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between features of augmented reality and user memorization

Abstract: The objective of this study is to investigate the relationship between the features of augmented reality (AR) and human memorization ability. The basis of this relation is derived from the following features. The AR feature is that AR can provide information associated with specific locations in the real world. The feature of human memory is that humans can easily memorize information if the information is visually associated with specific locations. To investigate this relation, we conduct a pilot user study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…AR has been shown in first experiments to support better memorization of items [21], [6], making use of spatial organization and the memory palace technique. Our study is in line with these promising results and shows that there can be a distinct benefit of AR for vocabulary learning, comparing with tried-and-true flashcard-based approaches.…”
Section: Virtual and Augmented Reality In Educationmentioning
confidence: 99%
“…AR has been shown in first experiments to support better memorization of items [21], [6], making use of spatial organization and the memory palace technique. Our study is in line with these promising results and shows that there can be a distinct benefit of AR for vocabulary learning, comparing with tried-and-true flashcard-based approaches.…”
Section: Virtual and Augmented Reality In Educationmentioning
confidence: 99%
“…Second, virtual pictures are two-dimensional (2D) and lack a three-dimensional (3D) perspective that would give learners a more comprehensive view. Third, experiencing a wholly virtual environment can be less instructive than experiencing a combination of real and virtual worlds (Fujimoto, Yamamoto, Taketomi, Miyazaki, & Kato, 2013; Zacharia, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of previous research have shown that AR applications have the following educational uses: supporting book readings (Hornecker & Dünser, 2007), making the learning experience more interactive and appealing (Fujimoto et al., 2013; Santos et al., 2016), increasing motivation (Di Serio, Ibáñez, & Kloos, 2013), drawing attention (Aziz, Aziz, Yusof, & Paul, 2012), establishing links with real life experiences (Ternier, Klemke, Kalz, Ulzen, & Specht, 2012), offering opportunities for more authentic learning and appealing to multiple learning styles (Yuen, 2011), and increasing learners’ performance in vocabulary expansion (Solak & Cakir, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Augmented reality offers many unique features that include; real-time display [6][8], interactive technology [17] [67] and information overlay on users' real-world view [22] [37]. There are many benefits of using augmented reality in enhancing education which include; in situ interactive visualization [7][54] [32], physical skills development [71], fun and entertainmentenhancement, [24][46], learning motivation improvement [24][15] [13] [58], and learning performance improvement [24][ [14][66].…”
Section: Introductionmentioning
confidence: 99%